Exploration of Elementary School Students’ Perceptions of the Effectiveness of Storytelling in English Learning - Samad, Ita Sarmita; Wahyuni, Sry; Hasriani G, Hasriani G (Majesty Journal, 2025)
English learning in primary schools still faces the challenge of low student motivation and engagement. One approach that is considered effective to overcome this is storytelling, This study aims to explore students’ perceptions of the use of storytelling methods in English language learning. This study uses descriptive quantitative approach with a survey method on 140 students in grades IV–VI SDN 013 Penajam. The instrument is a Likert scale questionnaire with 20 statements that cover two main dimensions: perceptions of the effectiveness of storytelling in English language learning and views on its social-emotional impact. Data were analyzed using descriptive statistics with the help of SPSS version 26 as well as thematic analysis for open-ended answers. The results showed that students had a very positive perception of the use of storytelling (M = 3.63). The highest aspect is storytelling that encourages imagination (M = 3.79), while the confidence aspect of speaking still needs to be strengthened. In addition to academic benefits, storytelling also increases empathy, cooperation, and the ability to express opinions. The qualitative analysis revealed four main themes: (1) learning becomes more enjoyable, (2) vocabulary comprehension increases, (3) courage and empathy develop, and (4) the expectation of more varied use of digital storytelling. Storytelling has been shown to be effective in improving motivation, contextual understanding, and social-emotional development of elementary school students. Therefore, the integration of storytelling and digital storytelling in the basic English curriculum is recommended as a humanistic, creative, and student-centered learning strategy.